2019
DOI: 10.1139/cjfas-2018-0399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, dissolved oxygen, and substrate on the development of metabolic phenotypes in age-0 lake sturgeon (Acipenser fulvescens): implications for overwintering survival

Abstract: The impact of early rearing environment on phenotypic development in teleosts has been reasonably well-documented, but only recently has attention been paid to sturgeon raised for conservation purposes. In the present study, we hypothesized that rearing environment will result in the development of distinct metabolic phenotypes in age-0 lake sturgeon (Acipenser fulvescens) and that these phenotypes will drive differential survival rates during a simulated overwintering event. Lake sturgeon gametes were fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 81 publications
0
26
2
Order By: Relevance
“…A simulated overwintering event was performed with changes in temperature and light intensity similar to what has previously been described (Yoon et al ., 2018) while DO remained constant within each treatment throughout the experimental period (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A simulated overwintering event was performed with changes in temperature and light intensity similar to what has previously been described (Yoon et al ., 2018) while DO remained constant within each treatment throughout the experimental period (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Previous results have indicated that acute exposure to hypoxia down to 80% of air saturation did not affect aerobic metabolism or hypoxia avoidance behaviours in a number of species of fish (Poulsen et al ., 2011; McBryan et al ., 2013; Svendsen et al ., 2014); however, long-term exposure to 80% dissolved oxygen (DO) could result in increased mortality and loss of aerobic capacity following exposure to a stressful environment (i.e. low temperature and food deprivation; Yoon et al ., 2018). Previous studies have predominantly focused on teleost fish (Fernandes et al ., 1995; Hobbs and Mcdonald, 2010), but these relationships remain poorly understood in ancestral fishes such as sturgeons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lake sturgeon chronically exposed to AC+PC had significantly lower Fulton's condition factor (p < 0.05) than chronic PC+C and control treatments (Fig. 4), which may impact overwinter survival in juvenile lake sturgeon (Yoon et al 2019).…”
Section: Cortisolmentioning
confidence: 96%
“…After spring spawning, juvenile lake sturgeon have a single season to grow before they endure their first overwinter challenge, which may last for at least 3 months with limited foraging opportunities and temperatures near 0°C (McDougall et al 2014). Such overwintering events have large consequences for survival and subsequent year-class strength as that cohort moves into the following year (Post and Evans 1989;Hurst and Conover 2003;Deslauriers et al 2018;Yoon et al 2019). Recent laboratory studies have demonstrated complex behavioural responses in juvenile lake sturgeon (Wishingrad et al 2014b(Wishingrad et al , 2014cFerrari et al 2015;Sloychuk et al 2016;Bjornson and Anderson 2018), but none have attempted to determine the trade-off between foraging and responding to predation threats in juvenile lake sturgeon.…”
Section: Introductionmentioning
confidence: 99%